Introduction: The Return of the Exception - Mańko, Rafał; Tacik, Przemysław; Fusco, Gian Giacomo (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The history of the 20th century, and more recently the two-decades long war on terror, have taught us the lesson that the normalisation of the state of exception (intended here as the proliferation of legal instruments regulating emergency powers, and their constant use in varied situations of crisis) is never immune from the risk of leaving long-lasting impacts of legal and political systems. With the “Return of the Exception” we intend to bring to the fore the fact that in the pandemic the state of exception has re-appeared in its “grand” version, the one that pertains to round-the-clock curfews and strong limitations to the freedom of movement and assembly, all adorned by warfare rhetoric of the fight against an invisible enemy – which, given the biological status of viruses, it cannot but be ourselves. But “return” here must be intended also in its psychoanalytic meaning. Much like the repressed that lives in a state of latency in the unconscious before eventually returning to inform consciousness and reshape behaviour, the state of exception is an element that remains nested in law’s text before reappearing in a specific moment with forms and intensity that are not fully predictable. Still, it remains cryptic whether the pandemic inaugurates a new epoch of liberal legality – the post-law – or just augurs its structural crisis.